Epicardial adipose tissue and carotid artery disease: Protocol for systematic review and meta-analysis. Issue 17 (April 2018) - Roever, Leonardo; Resende, Elmiro Santos; Diniz, Angélica Lemos Debs; Penha-Silva, Nilson; O'Connell, João Lucas; Gomes, Paulo Fernando Silva; Zanetti, Hugo Ribeiro; Roerver-Borges, Anaisa Silva; Veloso, Fernando César; de Souza, Fernanda Rodrigues; Duarte, Poliana Rodrigues Alves; Fidale, Thiago Montes; et al.
Abstract: Background: Atherosclerosis is now widely recognized as a multifactorial disease with outcomes that arise from complex factors such as plaque components, blood flow, and inflammation. Epicardial adipose tissue (EAT) is a metabolically active fat depot, abundant in proinflammatory cytokines, and has been correlated with the extent and severity of carotid artery disease (CD). The locations most frequently affected by carotid atherosclerosis are the proximal internal carotid artery (ie, the origin) and the common carotid artery bifurcation. Progression of atheromatous plaque at the carotid bifurcation results in luminal narrowing, often accompanied by ulceration. However, there are no systematic analyses or well-conducted meta-analyses to evaluate the relationship between EAT and CD. The aim of this study is to examine this association of EAT with CD in different ages and sex. Methods: This systematic review and meta-analysis will be conducted using published studies that will be identified from electronic databases (ie, PubMed, EMBASE, Web of Science, and Google Scholar. Studies that (1) examined the association between EAT and CD, (2) focus on cohort, case-control and cross-sectional studies, (3) will conducted among in adults aged 40 to 70 years, (4) provided sufficient data for calculating ORs or relative risk with a 95% CI, (5) will published as original articles written in English or other languages, and (6) have been published until January 2018 will be included. Study selection, data collection, quality assessment and statistical syntheses will be conducted based on discussions among investigators. Results: We propose the current protocol to evaluate the evaluation of EAT with ED. Conclusion: This systematic review will not need ethical approval, because it does not involve human beings. The results and findings of this study will be submitted and published in a scientific peer-reviewed journal. Ethics and dissemination: Ethics approval was not required for this study because it was based on published studies. The results and findings of this study will be submitted and published in a scientific peer-reviewed journal. Trial registration number: PROSPERO (CRD42018083458). Abstract : Supplemental Digital Content is available in the text